A abordagem do povo negro utilizada nos livros didáticos de História da Rede Salesiana de Escolas - Santos, Igor Iury Jurubeba (2020)
The production of teaching materials for elementary school has been increasingly improved. There are several efforts to understand the history of Africans and Afro-Brazilians as active historical agents. Therefore, the objective of this research was to analyze the approach of the black in the history textbook of the 7th year of elementary education of the Salesian Brazil School Network (RSB-Schools). This research was developed based on Law 10.639 / 03. An analysis of the texts and images of the textbooks of the Edebê publisher, including the Teacher's Manual, was carried out. The theoretical-methodological assumptions of Content Analysis (AC), was made according to Núcia Santoro, in the light of Laurence Bardin who defines what are the techniques for reading and interpreting content. There was a basis in the concepts of Choppin (2002), Rüsen (2011) and Bittencourt (2008), which enabled dialogues about the textbook. Munanga (2005), Joly (1999) and Muller (2009) were referenced in the theoretical contribution to the social representation of black people in textbooks. We sought to map situations in which blacks were included, or not, in school spaces through legislation. Finally, we analyze the content, to treat the information from a specific script through a pre-analysis. The purpose of this analysis as a whole is to favor the valorization of the identity, history and culture of black Brazilians and Africans in the new editions of textbooks, by expanding the focus of school curricula to reality pluriracial and cultural aspects of Brazilian society. It was possible to observe that the discipline of History in schools in Brazil went through several advances, until it was mandatory, and that the figure of the black person remembered serfdom and slavery, as a race inferior to that of its colonizers. This was shown through images and texts that portray the suffering of these peoples, which sometimes reflects prejudice in the students themselves. It is worth remembering that the Brazilian has a strong positive influence of African culture to the present day. The interpretation of the figure of the black in textbooks needs to improve in the sense of valuing their culture. Some figures require the teacher's intermediary for their correct interpretation, often described in the teacher's manual. All the interpretation of the content was developed, and the final product was made, a complementary e-book (online and free) bringing more complete information about some African peoples in order to point out the existence of the diversity of peoples with complex and different cultures in Africa, which shows not only the slavery suffered by these peoples in the past.